Kajian Perbandingan Tax Treaty Model: OECD, UN, dan US - Rachmawati, Dyna (Jurnal Widya Manajemen & Akuntansi, 2003)
The needs of tax treaty arise as international trade growth rapidly due to advancement of information technology. Taxa imposed on income derived from international trade are double. Tax treaty or tax convention is bilateral agreement for the avoidance of double taxation. This agreement arranges taxation rights. There are 3 (three) tax treaty model, which is used as reference to make bilateral agreement for the avoidance of double taxation. The first one is OECD Model made by The OECD Comittee of Fiscal. This model usually used by the OECD member, which is divided from developed countries. It is considered discriminative in tax imposing rights, especially for developing countries. The United Nations obligates to eliminate this discriminative by issuing UN Model in 1980. This is the second model and usually used by developing countries. The third model is US Model. This tax treaty is only used by United States to protect its interest in a board. As the first one borned, OECD Model is used as reference for both UN and US Model. Thus, this literature study used OECD Model as brainstorming in comparison. There are 2 (two) differences major between OECD Model and W Model. First, in OECD Model, there is an exclusive right in tax imposing on passive income. Second, limitations on lax imposing rights for source countries. The differences between OECD Model with US Model are basically caused by the needs of protection for US interest in aboard. So that, there are 3 (three) rules in US Model which aren't arranged by OECD Model. Those rules are: source of income, general rule of taxation and assistance of collection.